Weaving theory and practice: Design discourses, exchanges, and processes - Kristanti Dewi Paramita (Department of Architecture Faculty of Engineering Universitas Indonesia, 2021)
Theory and practice are often seen in opposition with one another in some architectural dialogues, despite their significant transformative capabilities. The first issue of ARSNET aims to dissolve such opposing relation by exploring how theory and practice weave and intersect in various architectural design inquiries. The articles in this issue investigate how the entanglements of theory and practice enable a precise reading of the contours of design knowledge, expand the interpretation of architectural spatialities, and drive a reflective awareness towards the progression of design processes.